2017
DOI: 10.1111/icad.12259
|View full text |Cite
|
Sign up to set email alerts
|

Sugar feeding of parasitoids in an agroecosystem: effects of community composition, habitat and vegetation

Abstract: Abstract. 1. Sugar from nectar or from honeydew can prolong parasitoids' lifespan, enhance their fecundity and foraging ability, and thereby increase their pest suppression efficiency. Sugar sources within crop monocultures are considered to be limiting for parasitoids. Nevertheless, only few studies have measured the sugar feeding of parasitoid assemblages in agricultural areas or in surrounding non-crop habitats.2. We used cold anthrone tests to compare the frequency of sugar feeding in parasitoid communitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 35 publications
2
15
1
1
Order By: Relevance
“…2), these effects were not consistent across all leek moth life stages or between years. This could be due in part to the dilution of any beneficial effect of nectar feeding by immigration of nectar-fed parasitoids from buckwheat plots into no-buckwheat plots, although the true dispersal abilities of the leek moth parasitoids are not known (Steppuhn and Wäckers 2004;Lee et al 2006;Kishinevsky et al 2018). Though not performed in this study, an analysis of the gut contents of parasitoids found in the no-buckwheat plots could help determine, in part, the extent of any parasitoid migration.…”
Section: Parasitismmentioning
confidence: 90%
“…2), these effects were not consistent across all leek moth life stages or between years. This could be due in part to the dilution of any beneficial effect of nectar feeding by immigration of nectar-fed parasitoids from buckwheat plots into no-buckwheat plots, although the true dispersal abilities of the leek moth parasitoids are not known (Steppuhn and Wäckers 2004;Lee et al 2006;Kishinevsky et al 2018). Though not performed in this study, an analysis of the gut contents of parasitoids found in the no-buckwheat plots could help determine, in part, the extent of any parasitoid migration.…”
Section: Parasitismmentioning
confidence: 90%
“…This is especially true in pro‐ovigenic parasitoids in which females emerge with their full egg supply and do not produce additional eggs during their lifetime (Jervis, Heimpel, Ferns, Harvey, & Kidd, 2001; Rivero & Casas, 1999). Several studies have demonstrated that parasitoids may be limited by sugar availability in the field (Heimpel & Jervis, 2005; Kishinevsky, Cohen, Chiel, Wajnberg, & Keasar, 2018; Segoli & Rosenheim, 2013c). Hence, a shortage of sugar sources is likely to increase the risk of time limitation, thereby selecting for higher allocation to initial energy reserves.…”
Section: Introductionmentioning
confidence: 99%
“…These sugar‐rich excretions are called honeydew, and honeydew production contributes to the regulation of osmotic stress during feeding . Honeydew can supply carbohydrates that stimulate oviposition and increase the survival and fecundity of predators and parasitoids . Honeydew also often serves as both an attractant and arrestant for foraging natural enemies, drawing them to prey and holding them in place once they arrive .…”
Section: Introductionmentioning
confidence: 99%
“…12 Honeydew can supply carbohydrates that stimulate oviposition and increase the survival and fecundity of predators and parasitoids. 8,13,14 Honeydew also often serves as both an attractant and arrestant for foraging natural enemies, 15,16 drawing them to prey and holding them in place once they arrive. 17,18 Indeed, it has been suggested that honeydew is the most abundant and accessible sugar resource available to natural enemies in agricultural fields.…”
Section: Introductionmentioning
confidence: 99%